2019
DOI: 10.3390/ijms20225679
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms and Posttranslational Modifications in Systemic Lupus Erythematosus

Abstract: The complex physiology of eukaryotic cells is regulated through numerous mechanisms, including epigenetic changes and posttranslational modifications. The wide-ranging diversity of these mechanisms constitutes a way of dynamic regulation of the functionality of proteins, their activity, and their subcellular localization as well as modulation of the differential expression of genes in response to external and internal stimuli that allow an organism to respond or adapt to accordingly. However, alterations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…These disorders include rheumatoid arthritis (RA), psoriasis, SLE, Alzheimer’s disease (AD), multiple sclerosis (MS), and cancers [ 68 ]. In SLE, the mechanisms responsible for the loss of immune tolerance have yet to be fully elucidated [ 70 ]; however, epigenetic factors and PTMs are becoming increasingly recognised in the pathogenesis of the disease [ 71 ]. In the context of SLE, the PTM of histone proteins, the loss of tolerance and the initiation of an autoimmune response are consistent features of the disease [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disorders include rheumatoid arthritis (RA), psoriasis, SLE, Alzheimer’s disease (AD), multiple sclerosis (MS), and cancers [ 68 ]. In SLE, the mechanisms responsible for the loss of immune tolerance have yet to be fully elucidated [ 70 ]; however, epigenetic factors and PTMs are becoming increasingly recognised in the pathogenesis of the disease [ 71 ]. In the context of SLE, the PTM of histone proteins, the loss of tolerance and the initiation of an autoimmune response are consistent features of the disease [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination, as an important form of the PTM of proteins, regulates protein abundance, activity, subcellular localization, and their interactions, as well as a variety of signaling pathways. Ubiquitination plays a pivotal role in the pathogenesis of SLE (132,133). A phase I clinical trial showed that the expression of Aiolos and Ikaros was significantly higher in patients with SLE than in healthy volunteers.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The PTMs found in patients with SLE include phosphorylation, methylation, acetylation, isoaspartylation, etc. The proteins susceptible to phosphorylation in SLE are U1 small nuclear ribonucleoprotein (snRNP) 68K [83], SSA/Ro and SSB/La [84,85], spliceosomal Sm protein that is vulnerable to methylation in D1 and D3 subunits [86,87], the frequently ubiquitinated proteinase serine/arginine-rich splicing factor 1 (SKSF1) [88] and myeloperoxidase (MPO) [89,90]. Table 4 lists the histone and non-histone protein modifications in immune-related cells and post-translational molecules in SLE patients.…”
Section: Post-translational Non-histone Protein Modifications In Slementioning
confidence: 99%